2021
DOI: 10.3390/polym13193279
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Foam Dressings Based on Gelatin, Hyaluronic Acid, and Carboxymethyl Chitosan Containing Fibroblast Growth Factor-7 for Dermal Regeneration

Abstract: Wound recovery close to the function of the native skin is the goal of wound healing. In this study, we prepared foam dressings (FDs; 2-GHC-FD-1–9, 5-GHC-FD-1–9, and 10-GHC-FD-1–9) composed of various concentrations of gelatin, hyaluronic acid, and carboxymethyl chitosan, which are chemically interconnected through amide bond formation, for evaluating wound healing. Tensile and cell proliferation tests showed that 2-GHC-FD-1–9 are suitable for wound dressing. For further evaluation, three types of FDs, 2-GHC-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Since the fucose content in DF can be obtained in the component analysis, we measured the concentration of fucose to estimate the dissociation of DF. The concentrations of fucose in the solutions were determined by the cysteine hydrochloride–sulfuric acid method with l -fucose as the standard …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the fucose content in DF can be obtained in the component analysis, we measured the concentration of fucose to estimate the dissociation of DF. The concentrations of fucose in the solutions were determined by the cysteine hydrochloride–sulfuric acid method with l -fucose as the standard …”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of fucose in the solutions were determined by the cysteine hydrochloride−sulfuric acid method with L-fucose as the standard. 21 2.5. Cytocompatibility and Hemocompatibility Investigation.…”
Section: Chemical Composition Of Dfmentioning
confidence: 99%
“…In order to construct a multifunctional dressing, we selected chitosan with hemostatic and antibacterial properties to make wound dressing. Chitosan, a derivative of chitin, the second rich polysaccharide in nature, possesses multiple properties, for instance, hemostasis, antisepsis, , and anti-inflammatory, promoting angiogenesis. , In addition, chitosan also has admirable physicochemical properties, , which can be used as an ideal carrier system for loading drugs such as cell growth factor and hyaluronic acid. In view of some inherent properties, chitosan has already been regarded as a potential material for biomedical applications. Our previously work exhibited that hydroxybutyl chitosan (HBCS, chemical structure is shown in Scheme ) homogeneously synthesized in alkali/urea aqueous solutions was a brilliant wound dressing. Cytocompatibility studies, using normal human dermal fibroblast (NHDF) cells, demonstrated that HBCS was nontoxic, even promoting the growth of fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping the wound area moist can be conducive to the micro-environment of wound healing, which is moderately moist, low oxygen, slightly acidic, clean surrounding environment, to accelerate the wound healing [ 8 ]. Hydrogels, foams, and films are used as biomaterials for wound healing and have good water absorption to keep the wound area moist [ 9 , 10 , 11 ]. The hydrogel has a three-dimensional hydrophilic polymer network connected by the covalent bond, hydrogen bond, van der Waals interactions, or other physical or chemical bonds [ 12 ].…”
Section: Introductionmentioning
confidence: 99%